ANALISIS EKSPERIMENTAL KINERJA POMPA SENTRIFUGAL TERHADAP VARIASI SISTEM PERPIPAAN DENGAN PENINJAUAN KERUGIAN TEKANAN MAYOR DAN MINOR - Kasturi Kasturi; Rezki Meilani (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study examines how variations in piping configuration affect the hydraulic performance of a horizontal centrifugal pump, using controlled tests on two pipe networks that differ in length and number/type of fittings. Flow rate and pressure were recorded at multiple valve openings and analyzed via the energy equation to separate major losses (Darcy–Weisbach) from minor losses (loss coefficient K). Results show that the system curve of Network 1 (longer pipe, more fittings) is steeper than Network 2, yielding lower operating flow and higher required head at identical valve set-points. Quantitatively, total discharge-line head loss reached 4.582 m, with minor losses, primarily from globe valves, elbows, and tees, dominating (>80%) over straight-pipe friction. Suction-side evaluation yielded NPSHa ≈ 29.584 m, indicating cavitation-free operation within the tested range. The findings confirm that engineering minor losses (reducing high-K fittings and optimizing bends) is more effective for lowering total head and moving operation toward the BEP than merely shortening the pipe. Practical recommendations include substituting globe valves for on–off duty, using large-radius elbows, and considering variable-frequency drives (VFDs) for energy-efficient flow control.